Lean Manufacturing Tools Training System - Mohamad, Effendi; Teruaki, Ito; Yuniawan, Dani (2013)
Lean Manufacturing (LM) implementation is essential to compete in today’s dynamic manufacturing environment. However, it is challenging to implement LM, mostly due to lack of know-how to implement the actual concept of LM and difficulty to choose a suitable LM tool for manufacturing processes. Traditional methods of LM training are inadequate to increase understanding of LM tools. This paper proposes a training framework that integrates Lean Manufacturing Tools Training System (LMTTS) with the current user training programme for LM tools. Consisting of the e-learning module and S-module (simulation module), LMTTS is a training system targeted to increase user’s comprehension and their confidence levels towards LM tools as well as enhancing overall training results of the LM tools. Each of these modules provides systematic information and simulation-based training on Single Minute Exchange of Die (SMED), Kanban, Poka Yoke, Preventive Maintenance, Autonomous Maintenance, Andon Light, Heijunka, and Cellular Manufacturing. This paper reports on LMTTS and its training procedure based on the new framework, focusing on an LM tool, i.e. SMED.